The Wall between the intention and writing mechanism in Architecture - Almaamouri, Abdullah Saadoon Salman; Abbas Ali Hamza; Laheeb Ali Alsaeg (Iraqi Journal of Architecture and Planning)
"The current search trying to study deeply the semantic relations generated from the adoption of mechanisms written with a certain intent on the board (the wall), as a means of displaying architectural text which is of semantically cumulative as it described as a traces .Where the Architected text is the writing about a topic not attaching pictures of the past and heritage. To establish by the search the structure of conceptual and assume to that a wall is not physically dividing line between inside and outside of the space but dialogue bridge between the designer and his intellectual reference at one side and the collective recipient’s memory in the context of a specific community in the other side, A dialogue reflected the change in the conceptual of cumulative written, and be far away from attaching pictures of the past which based on the structure similarity between the virtual vocabulary, toward the architected text depends on the structure of the difference, deals with the previous text as a traces opened a dialogue and multi-interpretation by the receiver, and then leading to a multiplicity readings and thus away from the wall for easy repetition mirroring the previous texts towards the speaking building in spite if a different languages for depending on designers and formats that generate them."